Changes in motor nerve excitability in acute phase Guillain‐Barré syndrome. Issue 4 (2nd February 2021) - Drenthen, Judith; Islam, Badrul; Islam, Zhahirul; Mohammad, Quazi D.; Maathuis, Ellen M.; Visser, Gerhard H.; van Doorn, Pieter A.; Blok, Joleen H.; Endtz, Hubert P.; Jacobs, Bart C.
Abstract: Background: The most common subtypes of Guillain‐Barré syndrome (GBS) are acute inflammatory demyelinating polyneuropathy (AIDP) and acute motor axonal neuropathy (AMAN). In the first days after the onset of weakness, standard nerve conduction studies (NCS) may not distinguish GBS subtypes. Reduced nerve excitability may be an early symptom of nerve dysfunction, which can be determined with the compound muscle action potential (CMAP) scan. The aim of this study was to explore whether early changes in motor nerve excitability in GBS patients are related to various subtypes. Methods: Prospective case–control study in 19 GBS patients from The Netherlands and 22 from Bangladesh. CMAP scans were performed within 2 days of hospital admission and NCS 7–14 days after onset of weakness. CMAP scans were also performed in age‐ and country‐matched controls. Results: CMAP scan patterns of patients who were classified as AMAN were distinctly different compared to the CMAP scan patterns of the patients who were classified as AIDP. The most pronounced differences were found in the stimulus intensity parameters. Conclusions: CMAP scans made at hospital admission demonstrate several characteristics that can be used as an early indicator of GBS subtype.